Pengaruh Suasana Toko, Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Apparel Di Awesam Store (Studi Kasus Awesam Store Kepanjen) - Ichsanuddin Akbar Atma Saputra; Achmad Agus Priyono; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of store atmosphere, price and product quality on purchasing decisions at Awesam Store. This research is a quantitative research. The method used for sampling is non-probability sampling with purposive sampling technique. The sample in this study were 80 consumers who had purchased products at the Awesam Store in December 2022 – February 2023. Data collection was carried out by observation, interviews and distributing questionnaires. Analysis of the data used in this study is using validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, F test, T test, and the coefficient of determination. Based on the results in this study indicate that simultaneously the variables store atmosphere, price, product quality, influence purchasing decisions. Partially, the store atmosphere variable influences purchasing decisions, price variables affect purchasing decisions, product quality influences purchasing decisions. Keywords: Store Atmosphere, Price, Product Quality, Purchase Decision